Unveiling the Role of High Glycemic Diets on Acne Formation - Aslam, Muhammad Bilal; Hafeez, Muhammad Adnan; Khan, Imad Ud Din (Indus Journal of Bioscience Research, 2025)
Background: Acne vulgaris is a prevalent dermatological condition that affects a significant proportion of the global population, particularly adolescents and young adults. Emerging research suggests that dietary factors, particularly high glycemic index (GI) diets, may play a crucial role in acne formation and severity. Western dietary patterns, characterized by excessive consumption of refined carbohydrates and processed foods, have been linked to an increased prevalence of acne. However, the exact mechanisms and strength of association remain a subject of investigation. Objective: This study aims to unveil the role of high glycemic diets in acne formation among university-going adults. By assessing dietary patterns and acne prevalence, this research seeks to establish a correlation between high GI food consumption and the severity and distribution of acne lesions. Methodology: A cross-sectional study was conducted among 180 university students from Punjab University, Superior University, Government College University Lahore, and the University of Lahore. Participants, aged 18-30 years, were selected through random sampling. Data collection involved dietary survey questionnaires and dermatological assessments. Acne severity, location, and type were recorded, and statistical analysis was performed to determine the association between high glycemic intake and acne formation. Results: The findings revealed a significant correlation between high glycemic diets and acne prevalence. Participants with severe high glycemic intake exhibited a higher incidence of acne (p=0.003), increased acne severity (p=0.006), and a predominance of facial acne (85%, p=0.025). Additionally, a notable distribution of acne types was observed, with blackheads (28%), whiteheads (30%), bumps (19%), and nodules (23%) being the most common presentations. Gender-wise, acne prevalence was higher in females (57%) compared to males (43%), with statistical significance (p=0.001). The overall acne formation rate in the study population was 53%, with 48% experiencing severe acne. Conclusion: The study confirms a strong association between high glycemic index diets and acne formation, severity, and location. A higher intake of refined carbohydrates and sugary foods contributes to increased insulin resistance, inflammation, and sebum production, exacerbating acne symptoms. The findings emphasize the importance of dietary modifications, particularly adopting low glycemic index foods, in acne management. Future research should focus on interventional studies to establish causality and explore dietary guidelines as a complementary approach to acne treatment.